2020
DOI: 10.1111/mec.15329
|View full text |Cite
|
Sign up to set email alerts
|

Ancient DNA suggests modern wolves trace their origin to a Late Pleistocene expansion from Beringia

Abstract: Grey wolves (Canis lupus) are one of the few large terrestrial carnivores that have maintained a wide geographical distribution across the Northern Hemisphere throughout the Pleistocene and Holocene. Recent genetic studies have suggested that, despite this continuous presence, major demographic changes occurred in wolf populations between the Late Pleistocene and early Holocene, and that extant wolves trace their ancestry to a single Late Pleistocene population. Both the geographical origin of this ancestral p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
147
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(163 citation statements)
references
References 74 publications
(99 reference statements)
13
147
2
1
Order By: Relevance
“…large Pleistocene individuals and more contemporary counterparts that were comparatively 273 diminutive (Meachen et al 2014). Response of canids to dietary shifts, demographic instability at 274 the glacial-interglacial interface, and wide-spread shuffling of distributions (Pardi and Smith 275 2016;Loog et al 2019) may have promoted interspecific contact. We suggest this scenario has 276 plausibility, given the emerging adaptive role for hybridization now commonly evoked in diverse 277 taxa (Lewontin and Birch 2006;Meier et al 2017;Jones et al 2018), to include canids (Kays et 278 al.…”
Section: Reconciling Conflict Among Genetic and Morphological Hypothementioning
confidence: 99%
“…large Pleistocene individuals and more contemporary counterparts that were comparatively 273 diminutive (Meachen et al 2014). Response of canids to dietary shifts, demographic instability at 274 the glacial-interglacial interface, and wide-spread shuffling of distributions (Pardi and Smith 275 2016;Loog et al 2019) may have promoted interspecific contact. We suggest this scenario has 276 plausibility, given the emerging adaptive role for hybridization now commonly evoked in diverse 277 taxa (Lewontin and Birch 2006;Meier et al 2017;Jones et al 2018), to include canids (Kays et 278 al.…”
Section: Reconciling Conflict Among Genetic and Morphological Hypothementioning
confidence: 99%
“…samples from before, during and after the demographic event of interest) and explicit statistical modelling that accounts for the randomness of individual loci and allows to formally consider the likelihood of different alternative demographic scenarios (e.g. [15,16]). Although ancient DNA alone already provides additional resolution that often enable researchers to exclude less likely scenarios (e.g.…”
Section: Pattern-based Approaches To Demographic Inferencementioning
confidence: 99%
“…A common question that can be addressed with ancient DNA is whether a present population is directly ancestral to a past population or if the latter has experienced admixture from external One way to overcome this problem is to use inference methods that allow explicit modelling of gene flow (e.g. in [49,15,58,16]). External lines of evidence, such as archaeological, linguistic and geographic information could be used to inform on the expected levels of gene flow to build a more realistic null model for testing continuity.…”
Section: Population Genetic Inference For Testing Population Continuimentioning
confidence: 99%
See 1 more Smart Citation
“…In this issue, Loog et al. (2020) undertake a more comprehensive mtDNA genome sequencing of 45 ancient wolves spanning the last 50,000 years and 95 modern wolves, worldwide. By testing 16 different spatially and temporally explicit demographic scenarios, the authors found support for an expansion from the geographic region spanning Beringia, Northeast of Siberia.…”
Section: Introductionmentioning
confidence: 99%